Bank funding stability, pricing strategies and the guidance of depositors - Schlueter, Tobias; Sievers, Soenke; Hartmann-Wendels, Thomas (Journal of Banking & Finance, 2015)
Banks face a ‘behavioralization’ of their balance sheets since deposit funding increasingly consists of non-maturing deposits with uncertain cash flows exposing them to asset liability (ALM) risk. Thus, this study examines the behavior of banks’ retail customers regarding non-maturing deposits. Our unique sample comprises the contract and cash flow data for 2.2 million individual contracts from 1991 to 2010. We find that contractual rewards, i.e., qualified interest payments, and government subsidies, effectively stabilize saving behavior and thus bank funding. The probability of an early deposit withdrawal decreases by approximately 40%, and cash flow volatility drops by about 25%. Our findings provide important insights for banks using pricing incentives to steer desired saving patterns for their non-maturing deposit portfolios. Finally, these results are informative regarding the bank liquidity regulations (Basel III) concerning the stability of deposits and the minimum requirements for risk management (European Commission DIRECTIVE 2006/48/EC).